Evaluating the Effect of Institutional Distance on the Bilateral Trade of China and EU - Bingxue Wang (Journal of World Economy, 2023)
Under the trend of global economic integration, in order to achieve China’s long-term goal of sustainable economic development, China is committed to strengthening its bilateral trade with countries around the world. The EU have long played an important role in China’s foreign trade, but there are still many problems in China’s bilateral trade with the EU. Therefore, many scholars have conducted a series of studies on the factors affecting bilateral trade between China and the EU in attempt to find positive economic and trade strategies to promote bilateral trade between China and the EU. At present, there is a growing consensus among scholars that is “institutions determine trade”. However, the results of previous studies do not provide a quantitative analysis of the impact of institutional distance on bilateral trade between China and the EU. Thus, the research on the impact of institutional distance on bilateral trade between China and the EU is rather one-sided. However, in fact, different categories of institutional distance may have different impacts. Therefore, this paper presents a classification study of the specific impact of institutional distance on bilateral trade between China and the EU.